The Different Scientific Approach to Extreme Left Terrorism in Spain and Italy: The GRAPO and the Red Brigades (Comillas Journal of International Relations, 2023)
At the end of the 1970s, Italy and Spain were among the western countries most affected by terrorism. Comparing the statistics of those years in Italy and Spain it turns out that in Spain the number of victims has been much higher than in the neighboring country. Most of the academic work has focused on ETA, overshadowing political violence moving from other ideologies. In the case of the GRAPO this is even more evident if we consider that its members killed more people than the Red Brigades and that, unlike the Italian organization, the academic studies on them are quite small. In this article we have compared both groups by looking at the scientific publications published on them, to demonstrate the different approaches used in Spain and Italy about this theme and the gap that exists at the scientific/academic level between GRAPO and BR. Finally, we have proposed possible research aims for the future.
Keywords: terrorism; GRAPO; Red Brigades; Italy; Spain